PENGEMBANGAN MEDIA ANIMASI BERBASIS MACROMEDIA FLASH PADA PELAJARAN FISIKA ALAT OPTIK - Doyan, Aris; Gunawan, Gunawan; Syukroyanti, Bq Azmi (IKIP Mataram, 2013)
Media is an important role in the learning process which will give effect to the understanding of the concepts and the learning result of students. Expected with the development of animation media based macromedia flash containing music and image features can provide a learning environment that is different from the usual. The purpose of this research is to develop an optical media-based animation tools of Macromedia Flash on the subjects of Physics Optical. The method used in this research is a method Research and development (R & D). The results show the development of media-based animation Macromedia Flash is needed creativity that generated media interest. The contents in the media based on the assessment of the three experts said optical media content animation tools are very good and worth using.